PELATIHAN KOMUNIKASI PEMASARAN PELAYANAN PRIMA BAGI PEMILIK HOMESTAY DI DESA MARGALUYU, BANDUNG) - Nada Arina Romli; Euis Puspita Dewi; Siti Sujatini; Sandy Allifiansyah (JURNAL ABDIMAS DOSMA (JAD), 2025)
Margaluyu Village is one of the tourist villages located in Bandung Regency, West Java, which has extraordinary natural potential. Margaluyu Village has long been inaugurated as a tourist village that is often a destination for domestic and foreign tourists. However, currently, there are not many homestay facilities in Margaluyu Village that have excellent hospitality service standards, so this activity aims to provide knowledge and skills to homestay owners regarding quality excellent service that can be provided by simple homestays. The methods used in this activity are socialization, training and counseling, as well as consultation and technical guidance. The stages of the activity begin with the preparation, implementation and evaluation stages. The focus of the material given to participants is on the elements of excellent service, namely on improving hospitality capabilities and creating tour packages for homestay owners.